Biocircular use of forest waste in native forests: economic analysis of the calden fachinales in La Pampa (Semiárida, 2024)
In the province of La Pampa, Argentina, a significant portion of the territory is occupied by xerophytic caldén forests. These forests have undergone an intense process of degradation due to inappropriate silvicultural and livestock management, resulting in bushy formations, of low productivity, called “shrub thicket”. With the aim of increasing livestock productivity and reducing the risk of wildfires, various interventions are carried out in these forests, generating forest residues that are often not utilized or harnessed. In this context, circular bioeconomy emerges as a conceptual framework challenging the linearity of the current economic model. It proposes the utilization of all residues and by-products from productive activities. The objective of this work is to economically analyze the potential use in the field of forest residues derived from interventions in the native forests of caldén. The estimated minimum and maximum quantities of potential forest residue generated by different interventions ranged between 33.12 and 44.81 Mg.ha-1. The costs necessary to make the waste available were estimated; economic-financial indicators were calculated to determine the necessary volumes to cover costs and achieve benefits. The circular utilization of forest residues from native forests is feasible, provided that viable scales are generated, and reference prices are attractive for agricultural producers and involved economic agents.
Keywords: forest biomass; bioeconomy; circular economy; variable costing